Blood Pressure and Renal Responses to Orthostatic Stress Before and After Radiofrequency Renal Denervation in Patients with Resistant Hypertension - Vuignier, Yann; Grouzmann, Eric; Muller, Olivier; Vakilzadeh, Nima; Faouzi, Mohamed; Maillard, Marc P.; Qanadli, Salah D.; Burnier, Michel; Wuerzner, Grégoire (Frontiers in Cardiovascular Medicine, 2018)
Background/Aims: In patients with resistant hypertension, renal denervation (RDN) studies have mainly focused their outcomes on blood pressure (BP). The aim of this study was to evaluate the long-term effect of RDN on neurohormonal profiles, renal hemodynamics and sodium excretion in a resting state and during stress induced by lower body negative pressure (LBNP). Materials and methods: This was a single center prospective observational study. Norepinephrine, plasma renin activity (PRA), glomerular filtration rate (GFR), renal plasma flow (RPF) and sodium excretion were measured in unstimulated conditions (rest) and after one hour of LBNP at three different time points: before (M0), one (M1) and twelve months (M12) after RDN. Results: Thirteen patients with resistant hypertension were included. In the resting state, no differences were observed in norepinephrine, PRA, sodium excretion and mean BP levels after RDN. GFR (78±32 ml/min at M0 vs 66±26 ml/min at M12 (p=0.012) and filtration fraction (22.6±5.4% at M0 vs 15.1±5.3% at M12 (p=0.002)) both decreased after RDN. During LBNP, the magnitude of the mean BP increase was reduced from +6.8±6.6 mm Hg at M0 to +2.3±1.3 mm Hg at M12 (p=0.005). The LBNP-induced increase in norepinephrine and decrease in GFR and sodium excretion observed before RDN were blunted after the procedure. Conclusion: A decrease in GFR and filtration fraction was observed one year after RDN. In addition, our results suggest that RDN blunts not only the norepinephrine but also the mean BP, the GFR and the sodium excretion responses to an orthostatic stress one year after the intervention.